معانقة اليأس وإكراهات الواقع:"قراءة في بعض قصائد فريدريش نيتشه" (مجلة إحالات, 2026)
Reality's persecutions had a beneficial return on Nietzsche's various writings. So that his writing styles varied to form an aesthetic mosaic hidden behind the surface of its significance, many existential problems that make the individual the focus of deep philosophical questions deep withinthe human essence. This is what our study, in which we will search for the causes of this philosopher,aims to embrace despair and coercion with reality.